Engineered pine endophytic Bacillus toyonensis with nematocidal and colonization abilities for pine wilt disease control - Li, Dongzhen; Li, Yongxia; Wang, Xuan; Zhang, Wei; Wen, Xiaojian; Liu, Zhenkai; Feng, Yuqian; Zhang, Xingyao (Frontiers in Microbiology, 2023)
Introduction The pinewood nematode (PWN) is responsible for causing pine wilt disease (PWD), which has led to the significant decline of conifer species in Eurasian forests and has become a globally invasive quarantine pest. Manipulating plant-associated microbes to control nematodes is an important strategy for sustainable pest management. However, it has proven difficult to find pine-associated bacteria that possess both nematocidal activity and the ability to colonize pine tissues. Methods The stress experiments with turpentine and pine tissue extract were carried out to screen for the desired target strain that could adapt to the internal environment of pine trees. This strain was used to construct an engineered nematocidal strain. Additionally, a fluorescent strain was constructed to determine its dispersal ability in Pinus massoniana seedlings through plate separation, PCR detection, and fluorescence microscopy observations. The engineered nematocidal strain was tested in the greenhouse experiment to assess its ability to effectively protect P. massoniana seedlings from nematode infection. Results This study isolated a Bacillus toyonensis strain Bxy19 from the healthy pine stem, which showed exceptional tolerance in stress experiments. An engineered nematocidal strain Bxy19P3C6 was constructed, which expressed the Cry6Aa crystal protein and exhibited nematocidal activity. The fluorescent strain Bxy19GFP was also constructed and used to test its dispersal ability. It was observed to enter the needles of the seedlings through the stomata and colonize the vascular bundle after being sprayed on the seedlings. The strain was observed to colonize and spread in the tracheid after being injected into the stems. The strain could colonize the seedlings and persist for at least 50 days. Furthermore, the greenhouse experiments indicated that both spraying and injecting the engineered strain Bxy19P3C6 had considerable efficacy against nematode infection. Discussion The evidence of the colonization ability and persistence of the strain in pine advances our understanding of the control and prediction of the colonization of exogenously delivered bacteria in pines. This study provides a promising approach for manipulating plant-associated bacteria and using Bt protein to control nematodes.